Sarcoidosis and sarcoidal foreign body reaction after permanent eye makeup application: Analysis by immunohistochemistry with commercially available antibodies specific to Cutibacterium acnes and Mycobacteria. (21st March 2022) - Hirai, Yuka; Hamada, Yuko; Sasaki, Shun; Suzuki, Marie; Ito, Yuta; Katayama, Keiko; Uno, Hirokazu; Nakada, Tokio; Kitami, Yuki; Uchida, Keisuke; Eishi, Yoshinobu; Sueki, Hirohiko
Abstract: We report two cases of eyebrow granulomas in patients who underwent a permanent eye makeup procedure. A rash was observed 16 months after the procedure in Case 1, and 10 years after the procedure in Case 2. Histopathologically, both patients exhibited noncaseating epithelioid cell granulomas. In Case 1, most of the black‐brown granules of the permanent makeup were not present in the granulomas but were localized in the upper dermis. In contrast, in Case 2, some of the black‐brown granules were phagocytized in the granulomas, preferentially within the giant cells. Based on systemic examinations, the patients from Cases 1 and 2 were diagnosed with sarcoidosis and sarcoidal foreign body reaction, respectively. To clarify the pathogenesis of our cases, we performed immunohistochemistry using commercially available monoclonal antibodies specific to Cutibacterium acnes, previously Propionibacterium acnes (PAB), and Mycobacteria (LAM antibody). PAB antibody results were positive in granulomas only in Case 1, and the LAM antibody results were negative in both cases. Immunohistochemical detection of C. acnes in granulomas could provide useful information for differentiating between cutaneous sarcoidosis and sarcoidal foreign body reactions.